HUBUNGAN ANTARA MOTIVASI KERJA PERAWAT DENGAN KEPUASAN KERJA PERAWAT DI INSTALASI RAWAT INAP BADAN RUMAH SAKIT UMUM DAERAH KABUPATEN BATANG - Anik Indriono; Zaenudin . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
Abstract This study is aimed at gaining information on the degree of nurses’work  motivation and nurses’work satisfaction in the inpatient ward and to know whether or not there is  a  correlation  between  the  two  variables.  Methode: This  study  belongs  to descriptive correlational study with cross sectional approach. The instrument used in this  study  is  questionnaire  given  to  55  nurses  in  the  inpatient  ward  of  BRSUD Kabupaten  Batang.  The  data  are  processed  and  analyzed  quantitatively  using univariat  and  bivariat  analysis.  The  Bivariat  analysis  uses  Rank  Spearman  test. Significance is determined by p-value < 0.05. Result: The results of the study shows that  sub variable of the nurses’ work motivation having significant  correlation with the  nurses’  work  satisfaction  is  the  motivation  of  power.  This  is  shown  by significance test where significance value (p-value is 0.029) < 0.05. This is probably because the respondents have the perception that working is a way to gain personal satisfaction by getting power and by using the power to ward others.Increasing  nurses’  work  motivation  and  nurses’  work  satisfaction  can  be understaken  through  the  management  of  BRSUD  Kabupaten  Batang  by  giving  job enrichment,  enlarging  participation  and  independence,  rotation  and  appropriate placement  according  to  their  competence,  giving  freedom  to  serve  patient  and  by acknowledgment and rewrd based on their achievement.Key words : Work motivation and work satisfaction